Memasuki Dunia Kerja/ Kuliah Dengan Career Planning - Noor Lita Sari; Antik Pujihastuti; Nunik Maya Hastuti; Reza Widiantoro; Resha Adi Pratama (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Vocational School is a level of secondary education which specifically prepares its graduates to be ready to work. Vocational school graduates are expected to be able to be absorbed and play a big role in the world of work. However, in reality there are still many vocational school graduates who have not been fully absorbed into the world of work. Based on data from the Central Statistics Agency (BPS), the Open Unemployment Rate (TPT) for vocational school graduates in Indonesia until November 2022 reached 11.41%, the highest among graduates at other levels of education. The high unemployment rate for vocational school graduates may be related to difficulties in determining career choices. The aim of the PkM activities at SMKN 1 Karanganyar is to help SMKN 1 Karanganyar students optimize their potential so that whatever their career goals are in the future will be achieved. Through this PkM activity, students at SMKN 1 Karanganyar are expected to be able to actualize themselves and align their potential regardless of the choices they make after graduating from SMKN 1 Karanganyar. The service method is carried out using educational methods about education, namely providing knowledge about the meaning of career planning, the benefits of career planning, the importance of career planning, tips for career success along with examples of career planning. Apart from this, training is also provided in making career planning as well as information on how to make a good job application letter, how to make an attractive CV, and tips on how to face job interviews and an introduction to job selection tests. The results of the service increase the knowledge of SMKN 1 Karanganyar students in terms of the world of work and education after graduating from school and can make good career plans for themselves.